2016
DOI: 10.1002/fut.21831
|View full text |Cite
|
Sign up to set email alerts
|

Trading Activity and Rate of Convergence in Commodity Futures Markets

Abstract: We analyze whether and how the trading activity of different trader types impacts the rate of convergence between spot and futures markets for a broad range of commodity futures markets over the 1999–2014 period. There is strong evidence that speculators (commodity index traders) increase (reduce) the rate of convergence between spot and futures markets. © 2016 Wiley Periodicals, Inc. Jrl Fut Mark 37:930–938, 2017

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…168, no. 1100(September 2017 Senior management at the International Monetary Fund (IMF) including Christine Lagarde offer their opinions about its latest initiatives and what the future holds. The IMF continues to provide financial support such as the €1.6 billion programme announced for Greece but the Fund is also keen to emphasise the third pillar of its mandate which is capacity development and seeks to nurture institutions and talent that will sustain long-term development.…”
Section: /34mentioning
confidence: 99%
See 1 more Smart Citation
“…168, no. 1100(September 2017 Senior management at the International Monetary Fund (IMF) including Christine Lagarde offer their opinions about its latest initiatives and what the future holds. The IMF continues to provide financial support such as the €1.6 billion programme announced for Greece but the Fund is also keen to emphasise the third pillar of its mandate which is capacity development and seeks to nurture institutions and talent that will sustain long-term development.…”
Section: /34mentioning
confidence: 99%
“…168, no. 1100(September 2017 Catastrophic disasters at Chernobyl in 1986 and Fukushima in 2011 have seemingly done little to quell the appetite for nuclear power throughout the world. Indeed, more new nuclear plants came online in 2016 than in any year since the 1980s.…”
Section: /34mentioning
confidence: 99%
“…Furthermore, Floros and Vougas (2008) and Demir, Martell and Wang (2019) suggested that there is a significant relationship between cash and futures markets and both markets have predictive power for each other, making the relationship bi-directional (Kawaller, Koch & Koch, 1987). Bosch and Pradkhan (2017) suggested that trading activity of non-commercial traders increases rate of convergence in both markets. Korn, Krischak and Theissen (2019) stated that illiquidity in futures market increases with increase in illiquidity in cash market.…”
Section: Introductionmentioning
confidence: 99%